Pendidikan yang Memanusiakan: Sastra Pembebasan terhadap Dominasi dan Penindasan dalam Trilogi Puisi-Perempuan Abdul Wachid B.S. - Kholid Mawardi (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
women-poem trilogy of Abdul Wachid B.S. is a work that builds on the basis class perspective, with critical education paradigm approach. These three poems describe clearly how literary work can have function to empower oneself and placed him on liberation horizon, through humanizing education. Analytical studies from those poems clarify that literary work that neglect social reality will lose empowerment and liberation meaning.Â